Evaluating the Impact of Rubrics on Microteaching Skills and Teaching Competencies Among Prospective Teachers - Rajni; Prof. (Dr) Vijay Phogat (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study investigates the impact of rubric-based evaluation tools on the microteaching skills and teaching competencies of prospective teachers. Rubrics are essential in teacher education for establishing clear, measurable criteria for performance assessment, which is crucial in developing effective teaching practices. This research utilizes a quasi-experimental design to explore how structured feedback through rubrics can enhance pedagogical skills such as lesson planning, delivery, student engagement, and reflective practices. Findings indicate that rubrics significantly improve microteaching performance by providing targeted feedback that helps refine teaching techniques. The use of rubrics also promotes a better understanding of educational standards among teacher candidates, facilitating their professional development and preparation for real classroom challenges. This study highlights the value of rubrics in teacher training programs, suggesting they are vital for elevating educational quality through improved instructional practices. Furthermore, the adoption of rubrics encourages a more constructive dialogue between educators and students. Feedback sessions become more focused and productive, as they are anchored in clearly defined criteria and observable outcomes. This specificity not only enhances the instructional feedback but also helps in building a supportive learning environment where prospective teachers feel valued and understood. The implementation of rubric-based evaluations in teacher training not only sharpens microteaching skills but also significantly contributes to the holistic development of teaching competencies. By integrating rubrics into the assessment process, educational institutions can better equip future teachers with the necessary skills and knowledge to meet the diverse needs of their future classrooms, ultimately leading to improved educational outcomes. The broader implications of integrating rubric-based evaluations extend beyond immediate pedagogical improvements, touching upon the professional identity formation of prospective teachers. As these educators engage with rubrics, they not only acquire specific teaching skills but also develop a professional ethos grounded in reflective practice and accountability. This shift in perspective is critical for the development of teachers who are not only skilled but also adaptable and responsive to the evolving educational landscape. In addition, the systematic application of rubrics can facilitate collaborative learning environments where peer feedback becomes an integral part of teacher education. Such environments encourage prospective teachers to engage in peer assessments, which can deepen their understanding of teaching competencies and expose them to diverse educational strategies and perspectives. This collaborative approach helps build a community of practice that supports lifelong learning and professional growth. Finally, this study suggests that for rubrics to be most effective, they must be carefully designed to align with the specific competencies that teacher education programs aim to develop. They should also be flexible enough to adapt to various teaching contexts and learner needs. The ongoing refinement and adaptation of rubrics based on empirical evidence and feedback from educators and students will be essential for maximizing their potential in teacher education.
Keywords: Educators; Rubric-Based Evaluation Tools